2021
DOI: 10.1093/jas/skab280
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial DNA identified in abscessed and non-abscessed bovine hepatic tissue at the time of harvest

Abstract: Bacteriological characterization of bovine liver abscesses has been accomplished by cultural methods but DNA methods are still needed, as many bacteria are not conducive to laboratory culture. In addition to this gap in research, there have been no studies which identify the bacterial presence within healthy, non-abscessed liver tissue. The objective of this study was to compare the bacteriome of both abscessed and non-abscessed bovine livers in an observational case-control study design. Fifty-six livers, obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…By triggering the release of a vast number of inflammatory cytokines in various cell types, LPS can cause significant inflammation (Ngkelo, Meja et al 2012). Quite interestingly, Proteobacteria was identified as one of the predominant phylum in non-abscessed livers (Stotz, Henry et al 2021), consistent with the report that this phylum is dominant in the rumen (Mann, Wetzels et al 2018).…”
Section: Core Microbial Taxa Identified In the Liversupporting
confidence: 78%
See 1 more Smart Citation
“…By triggering the release of a vast number of inflammatory cytokines in various cell types, LPS can cause significant inflammation (Ngkelo, Meja et al 2012). Quite interestingly, Proteobacteria was identified as one of the predominant phylum in non-abscessed livers (Stotz, Henry et al 2021), consistent with the report that this phylum is dominant in the rumen (Mann, Wetzels et al 2018).…”
Section: Core Microbial Taxa Identified In the Liversupporting
confidence: 78%
“…Though T. pyogenes is a commensal bacterium, it is a common opportunistic pathogen, which causes purulent or necrotic lesions in several different tissues, including uterus (Amos, Healey et al 2014, Bicalho, Lima et al 2016, mammary gland (Madsen, Aalbaek et al 1992, Rezanejad, Karimi et al 2019, liver (Tadepalli, Narayanan et al 2009), and hoof (Kontturi, Junni et al 2019). Stotz and coauthors (Stotz, Henry et al 2021) reported Tenericutes was identified as a dominant phylum second to Fusobacteria and Bacteroidetes in severely abscessed liver samples. In the same study, Cyanobacteria was identified as the dominant phyla in non-abscessed and scarred liver samples.…”
Section: Core Microbial Taxa Identified In the Livermentioning
confidence: 99%
“…While Fusobacteria-dominated communities were still by far the most common, Bacteroidetes-dominated communities represented almost a quarter (23%) of the abscesses sampled in this study. When compared across treatment groups in previous 16S sequencing studies, members of Bacteroidetes were the second or third most abundant phyla after Fusobacteria within abscesses ( Weinroth et al, 2017 ; Amachawadi et al, 2021 ; Stotz et al, 2021 ) but have not previously been demonstrated as the dominant members of individual abscesses. Within these Bacteroidetes-dominated communities, the genera Bacteroides and Porphyromonas were the most abundant, species of which have previously been isolated from LAs.…”
Section: Discussionmentioning
confidence: 80%
“…Members of Acinetobacter , Campylobacter , Helocococcus , Parvimonas , Pseudomonas , and Psychrobacter have all been associated with wound infections in the gut ( Collins et al, 2004 ; Eliopoulos et al, 2008 ; Price et al, 2009 ; Okuda et al, 2010 ; Kaakoush et al, 2014 ), and despite their differential abundance between abscesses community type, their presence in LAs further emphasizes the importance of keeping a polymicrobial perspective when considering causes and potential prevention strategies for LA syndrome in cattle. Trueperella is commonly identified as a predominant microbial community member and considered a potential secondary etiological agent of bovine LAs ( Reinhardt and Hubbert, 2015 ; Weinroth et al, 2017 ; Stotz et al, 2021 ), and its increased abundance in Bacteroidetes-dominated LAs is an important finding that emphasizes the importance of discriminating between community types in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation